Kinesio taping for chronic low back pain: A systematic review. Issue 3 (July 2016) - Nelson, Nicole L.
Summary: Background: Chronic low back pain (CLBP) is a prevalent issue that engenders enormous social and economic burdens. Recently, kinesio taping (KT) has become of interest in the management of chronic pain. Accordingly, this is the first systematic review to explicitly report the effects of KT on CLBP. Objective: The aim of this review was to summarize the results of randomized controlled trials (RCTs) investigating the effects of KT on CLBP. Methods: A search was performed on the electronic databases PubMed, MEDLINE, SPORT Discus and Science Direct, up to June 17, 2015, using the following keywords: Kinesiology taping, kinesio taping, chronic low back pain. Results: In total, five studies involving 306 subjects met the inclusion criteria and corresponded to the aim of this review. The methodological quality of the included RCTs was good, with a mean score of 6.6 on the 10-point PEDro Scale. Moderate evidence suggests KT, as a sole treatment or in conjunction with another treatment, is no more effective than conventional physical therapy and exercise with respect to improving pain and disability outcomes. There is insufficient evidence suggesting that KT is superior to sham taping in improving pain and disability. Limited evidence suggests that KT is more effective than sham taping in improving range of motion (ROM) and global perceived effect (GPE) in the short term. Very limited evidence indicates that KT is more effective than conventional physical therapy in improving anticipatory postural control of the transversus abdominus muscles and improved cerebral cortex potential. Conclusion: Kinesio taping is not a substitute for traditional physical therapy or exercise. Rather, KT may be most effective when used as an adjunctive therapy, perhaps by improving ROM, muscular endurance and motor control. More high quality studies that consider the multiple factors that mediate CLBP, in the short, intermediate and long term, are needed to strengthen the evidence of the effectiveness of KT on CLBP. Systematic review registration: PROSPERO CRD42015023837